Penerapan Asas Individualiteit terhadap Sistematika Berjalannya Hukum Kebendaan di Masyarakat Indonesia - Al Qodar Purwo Sulistyo; Anang Dony Irawan; Titi Mahira A’dawiyah; Rosita Indriani; Muhammad Nur Hidayat (Universitas Ahmad Dahlan, 2023)
The existence of material law is very important in a social life. With the existence of material law all objects can be regulated so as to create a life that respects each other regarding material possessions and power over their owners. Of course material rights are based on statutory provisions so that they are binding. So that its existence provides things that need to be obeyed by the community in order to achieve a welfare state or a welfare state in accordance with the ideals of the state. With this basis, the principle of individuality can certainly be realized in society through material law because it is based on existing laws. The effectiveness of the principle of individuality can be realized on the basis of the existence of applicable laws and regulations, as stated in Law Number 12 of 2011. With the existence of applicable material law, it certainly has a full effect on people's lives, where people must obey and submit and comply with all rules. law especially in the implementation of statutory regulations that have been stipulated. So that the enforcement of the law of objects based on the principle of individuality can run in accordance with existing provisions. This principle makes it easier for the community to claim their ownership rights to an object because according to this principle the rights to objects can be determined individually. The right to own an object means the right to enjoy an object freely and regarding this property right is very necessary for the community so that problems do not occur in the future. The research contribution is expected that these guarantees will later become two parts, namely material (material) guarantees in the form of absolute rights to an object and can be maintained and transferred and immaterial (individual) guarantees which only cause direct relationships to certain individuals. This research method uses normative juridical, using a journal literacy approach using materials in the form of legal principles, related basic laws as primary or principal legal materials in completing this research. The systematic application of object law based on the principle of individuality can be carried out because it has been determined and ratified by the legislature with the approval of the president, of course.